PENGARUH PENGGUNAAN TEPUNG DAUN PEPAYA (Carica papaya L) DALAM RANSUM TERHADAP PENAMPILAN AYAM PEDAGING - Sarjuni, Sri; Mozin, Selvy (FAPETKAN UNTAD, 2011)
The research was aimed to examine the effect of papaya leaf powder in diets on feed consumption, weight gain and feed conversion ratio of broiler chicken. The research was conducted in Experimental Farm of Animal Science Department, Agriculture Faculty, Tadulako University. Â Â A Completely Randomized Design (CRD) was applied in this research. The treatment consist of five treatments with six replicates: (i) basal diets; diets with 3% of papaya leaf powder; (ii) diets with 6% of papaya leaf powder; (iii) diets with 9% of papaya leaf powder; and (iv) diets with 12% of papaya leaf powder. Data was analyzed by variance analysis based on experimental design. Results showed significant effect (P < 0.05) on feed consumption, weight gain and feed conversion of broiler chicken. The best results from this experiment were found in the diets with 9% of papaya leaf powder. Key words: Broiler, feed consumption, papaya leaf powder, weight gain.